KONSEP KESEHATAN MENTAL DALAM AL-QUR’ĀN DAN IMPLIKASINYA TERHADAP ADVERSITY QUOTIENT PERSPEKTIF TAFSIR AL-MISBAH - Samain sam (IAIN Bone, 2020)
The objectives of this paper are: (1) How is the concept of mental health in the Qur'an, (2) How is the view of the Qur'ān about psychotherapy on mental health disorders. (3) What are the implications of the concept of al-Qur'ān on mental health against the attitude of the Adversity Quotient from the perspective of Al-Misbah's interpretation. This research is a qualitative study using the theoretical method of text hermeneutics. The results of this study indicate that the al-Qur'ān contains spiritual values so that it can overcome the difficulties of human life. The view of al-Qur'ān about psychotherapy is a model of healing with rukyah in accordance with the surah Al Isra '(17): 82. The essential implications of adversity Quotient Mental health contained in al-Qur'ān surah al-Baqarah (2): 153; al-Baqarah (2): 155; and Adz Dariyat: 56. These verses contain strong values and motivation for adversity quotient, namely patience and optimism. The results of this study are expected to be able to reconstruct a human perspective and a healthy mentality in facing life's problems so that they have a high Adversity Quotient and are not easily discouraged, resilient, abstinence and not easy to commit suicide.Keywords: Mental Health, Adversity Quotient, Tafsir Al Misbah